Estudo da modulação autonômica cardíaca no processo de envelhecimento e suas relações com a terapia de reposição hormonal, proteína C-reativa e comprimento de telômeros - Perseguini, Natália Maria (2014)
The aging process affects many systems of the human body, including: autonomic nervous system, which can be assessed by heart rate variability (HRV); cellular structures, such as telomere length; and mechanisms of regulation of the inflammatory process, which can be evaluated by inflammatory markers such as high-sensitivity C-reactive protein (hsCRP). The combined analysis of these variables enables the study of the aging process in a multidimensional way. Additionally, the effects of hormone replacement therapy (HRT) on HRV are contradictory. In this way, we conducted the study I, which aimed to investigate the effects of HRT on HRV in healthy postmenopausal women. Two groups were evaluated: Group 1 (G1): 20 women who did not use HRT (60 ± 5.89 years) and group 2 (G2): 20 women undergoing HRT (59 ± 5.70 years). The electrocardiogram was recorded in supine position for 10 min. Spectral analysis included low and high frequency in absolute (LF and HF) and normalized (LFnu and HFnu) units. LF/HF ratio was also calculated. Symbolic analysis (0V%, 1V%, 2LV% e 2UV%), Shannon and conditional entropy were calculated. LF, LFnu and LF/HF ratio were higher, whereas HFnu was lower in G2 than in G1. Correlations between complexity indices and HFnu were significant and positive only in G1. We conclude that women undergoing HRT had higher cardiac sympathetic modulation and reduced cardiac vagal modulation compared to women not using HRT. Moreover, the expected positive relationship between cardiac vagal modulation and HRV complexity was found only in the group not undergoing HRT, indicating that vagal modulation in women under therapy drop below a minimum value necessary to the association to become apparent, suggesting an unfavorable cardiac autonomic modulation in spite of HRT. Considering the findings of the study I, we chose to adopt the use of the therapy as an exclusion criterion for the study II. Thus, the study II aimed to examine the aging effect on heart rate variability in supine and standing, on serum hsCRP and leukocyte telomere length, as well as to verify the age at which the changes caused by aging process are accentuated. One hundred and ten volunteers were divided into five groups according to age: G21-30 years, G31-40 years, G41-50 years, G51-60 years, and G61-70 years. Venous blood samples were collected for measurements of serum hsCRP and telomere length. ECG signals were recorded in rest supine and standing (15 min in each posture). HRV was assessed by spectral analysis in low and high frequencies in absolute (LF e HF) and normalized (LFnu e HFnu) units; symbolic analysis (0V%, 1V%, 2LV% e 2UV%); Shannon entropy; and complexity index (CI) and normalized CI (NCI) from conditional entropy. The main results were: 1) HF and 2UV% reduction (vagal modulation) in G51-60, and 0V% increase (sympathetic modulation) and NCI reduction (complexity) in G61-70, in supine; 2) less efficient response to postural change from supine to standing with advancing age; 3) hsCRP increase in G51-60; 4) telomere shortening in G61-70; 5) in supine, HRV indices showed stronger relationship with the principal component of most relevance from the multivariate principal component analysis, compared to hsCRP and telomere length. Considering that HRV indices in supine had a stronger association with the aging process, we can conclude that the decrease in cardiac vagal modulation may have influenced the increase in serum hsCRP (although normal values), in G51-60, since this effect is described by the cholinergic anti-inflammatory pathway. Decreased cardiac vagal modulation and increased hsCRP may have contributed to the telomere shortening identified in the following decade (G61-70). In this way, we must consider the importance of preventive actions prior to the onset of aging effects, particularly in the 41-50 age range, in an attempt to attenuate the natural effects of senescence.